Molecular Imprinted Polymers on Microneedle Arrays for Point of Care Transdermal Sampling and Sensing of Inflammatory Biomarkers - Sanjiv Sharma (ACS Omega, 2022)
The skin interstitial fluid (ISF) contains biomarkers that complement other biofluids such as blood, sweat, saliva, and urine. It can be sampled in a minimally invasive manner and used either for point of care testing or real time, continuous monitoring of analytes, the latter using microneedle arrays. The analytes present in the skin ISF are indicative of both systemic and local (i.e., skin) physiology. In this paper, we describe combining microneedle technology with molecularly imprinted polymers to demonstrate the potential of transdermal electrochemical sensing. The molecularly imprinted polymer employed here is easy to produce; it can be thought of as plastic antibody. Its synthesis is scalable, and the resulting sensor has a short measurement time (6 min), with high accuracy and a low limit of detection. It provides the requisite specificity to detect the proinflammatory cytokine IL-6. IL-6 is present in the skin ISF with other cytokines and is implicated in many clinical states including neurodegenerative diseases and fatal pneumonia from SARSCoV 2. The ability to mass produce microneedle arrays and plastic antibodies will allow for low-cost transdermal sensing devices. The transdermal sensors were able to detect IL-6 at concentrations as low as 1 pg/mL in artificial skin ISF, indicating its utility for routine point of care, bloodless measurements in simpler settings, worldwide.